(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
Immune reconstitution inflammatory syndrome (IRIS), an overwhelming inflammatory response to antigens in patients with rapidly recovering immune system is a life-threatening medical condition. Literature search for this topic was done on Google Scholar Database using terms such as: immune reconstitution inflammatory syndrome, immune restoration inflammatory syndrome, immune recovery syndrome OR immune restoration disease (#1) and HIV/AIDS (#2), TB (#3) OR Cryptococcus (#4). Articles published in the last twenty years in human studies with infectious causes linked to the developing IRIS were selected while those older than twenty years or which neither involve humans nor had noninfectious causes were excluded. A total of 51 papers were therefore reviewed and findings showed that essentially, viruses (HIV, JC, cytomegalovirus), fungi (Histoplasma species and Cryptococci), protozoans (Leishmania species) and mycobacteria (M. tuberculosis, Mycobacterium leprae) are the pathogens which cause most forms of antigensspecific IRIS. There was no common pathophysiological explanation for all forms of IRIS but the syndrome is largely driven by cytokine production leading to an unbalanced immune reconstitution of effector and regulatory T cells in patients undergoing rapid immune reconstitution. Understanding of possible risk factors for the development of IRIS as well as its pathogenesis and presentation is key to its management and prevention.